2019
DOI: 10.1038/s41477-018-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

Stout camphor tree genome fills gaps in understanding of flowering plant genome evolution

Abstract: We present reference-quality genome assembly and annotation for the stout camphor tree (Cinnamomum kanehirae (Laurales, Lauraceae)), the first sequenced member of the Magnoliidae comprising four orders (Laurales, Magnoliales, Canellales and Piperales) and over 9,000 species. Phylogenomic analysis of 13 representative seed plant genomes indicates that magnoliid and eudicot lineages share more recent common ancestry than monocots. Two whole-genome duplication events were inferred within the magnoliid lineage: on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
188
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(222 citation statements)
references
References 102 publications
31
188
3
Order By: Relevance
“…This contrasts with recent studies in magnoliids (Chaw et al 2019;Chen et al 2019), where the authors found WGD with lower Ks values (thus potentially more recent), and hypothesized them to be shared in magnoliids and thus older than the divergence between Lauraceae and Magnoliaceae.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…This contrasts with recent studies in magnoliids (Chaw et al 2019;Chen et al 2019), where the authors found WGD with lower Ks values (thus potentially more recent), and hypothesized them to be shared in magnoliids and thus older than the divergence between Lauraceae and Magnoliaceae.…”
Section: Resultscontrasting
confidence: 99%
“…In addition to the standard GMM method, we also used the BGMM method and confirmed that fitting more complex Gaussian models only resulted in components of negligible weights (results not shown). Considering two components for Annona and Liriodendron, and twothree components for Cinnamomum (as indicated by the results above), the main peak in Annona was found around 1.3-1.5 Ks units, whereas it occured around 0.8 Ks units (two components) or 0.4 and 1.3-1.4 Ks units (three components) in Cinnamomum (partially comparable -for the two components -with results from previous studies (Chaw et al 2019), as we did not identify a peak at 0.76). Notably, the oldest peak in…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations